A Specific Immunologic Assay for Functional Plasminogen Activator Inhibitor 1 in Plasma – Standardized Measurements of the Inhibitor and Related Parameters in Patients with Venous Thromboembolic Disease - Philips, Malou; Juul, Anne-Grethe; Selmer, Johan; Lind, Bent; Thorsen, Sixtus (Thrombosis and Haemostasis, 1992)
A new assay for functional plasminogen activator inhibitor 1 (PAI-1) in plasma was developed. The assay is based on the quantitative conversion of PAI-1 to urokinase-type plasminogen activator (u-PA)-PAI-l complex the concentration of which is then determined by an ELISA employing monoclonal anti-PAI-1 as catching antibody and monoclonal anti-u-PA as detecting antibody. The assay exhibits high sensitivity, specificity, accuracy, and precision. The level of functional PAI-1, tissue-type plasminogen activator (t-PA) activity and t-PA-PAI-1 complex was measured in normal subjects and in patients with venous thromboembolism in a silent phase. Blood collection procedures and calibration of the respective assays were rigorously standardized. It was found that the patients had a decreased fibrinolytic capacity. This could be ascribed to high plasma levels of PAI-1. The release of t-PA during venous occlusion of an arm for 10 min expressed as the increase in t-PA + t-PA-PAI-1 complex exhibited great variation and no significant difference could be demonstrated between the patients with a thrombotic tendency and the normal subjects.